Simulation-based estimation of dosimetric quantities for different phantom compositions and the effectiveness of aluminum shielding against galactic cosmic rays - Rohit Yadav; Sandipan Dawn; A. K. Bakshi; B. K. Sapra (Radiation Protection and Environment)
Astronauts on space missions are exposed to high radiation levels, especially from galactic cosmic rays (GCRs), which consist of particles with high energy such as protons, helium ions, and heavy ions. Accurate estimation of the dosimetric impact of GCR on human organs is crucial for radiation protection during these missions. In the present study, dosimetric parameters such as absorbed dose rate, dose equivalent rate, and average quality factor (<Q>) were estimated for different organ compositions from two phantoms: the ICRP 110 voxel phantom and the computerized imaging reference system (CIRS) ATOM series phantom using Monte Carlo simulation code FLUKA. A 10 cm target sphere with varying organ compositions was irradiated by GCRs at a solar modulation of Φ =465 MV. With an average absorbed dose rate of 0.435 mGy/day and a dose equivalent rate of 1.75 mSv/day without any shielding, the results show that the absorbed dose rate, dose equivalent rate, and < Q> values for the compositions of both the phantoms were nearly identical. Despite differences in elemental composition, the two phantoms show only minor variations in dosimetric quantities, validating the use of CIRS ATOM series phantoms as reliable alternatives for space radiation studies. The effectiveness of aluminum shielding was also evaluated, showing a small increase in absorbed dose rate with shielding thickness (from 0.40 mGy/day without shielding to 0.48 mGy/day at shielding thickness of 50 g/cm²). While the dose equivalent rate decreased from 1.47 mSv/day without shielding to 0.98 mSv/day at 20 g/cm², before increasing again due to neutron build-up. A dose equivalent rate minimum was observed at 20 g/cm², aligning with results reported in previous studies. A decreasing trend was also observed in the results of < Q>, highlighting the conversion of high linear energy transfer (LET) to low LET particles. This study also highlights the importance of accurate organ-specific dosimetry and Monte Carlo simulations for modeling radiation exposure during space missions.